Pembuatan Bibliografi Beranotasi Karya Ilmiah Mahasiswa S2 di Perpustakaan Program Magister Manajemen Fakultas Ekonomi Universitas Negeri Padang - Trifani, Prilia; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
The method used descriptive method with data collection through direct observation or observation. The observations were made by collecting and recording a collection of theses contained in the Library Faculty of Economic to Master of Manegement State Universtyof Padang. Based on direct observation number of theses in the library collections Master of Management Program In Economics Falkutas Negeri Padang is 89 Thesis.Based on the discussion can be concluded the stage of making an annotated bibliography of scientific works S2 is as follows: First, determination of the title to see: (a) see the library collection; (b) the need for the library collection by the user; (c) the information that is most in demand or a much-needed user, Second, the collection of library materials. Third, the selection of library materials, the selection aims to samples collected in accordance with the title or topic that has been set. Fourth, grouping or classification . Fifth, Manufacture of keywords, Manufacture of keywords generation aimed for users directly see the information of needed by looking at certain subjects that have been registered. Sixth, arrangins of index aims to facilitate users to refound the word or term contained in the bibliography. Seventh, typing bibliographies script by using the writing state of written Psycology Assosiation (APA). Keyword: Descriptive, bibliography, observation